Hands-On Embedded Programming with C++17 - Posch, Maya (Packt Publishing, 2019)
Build safety-critical and memory-safe stand-alone and networked embedded systems Key Features Know how C++ works and compares to other languages used for embedded development Create advanced GUIs for embedded devices to design an attractive and functional UI Integrate proven strategies into your design for optimum hardware performance Book Description C++ is a great choice for embedded development, most notably, because it does not add any bloat, extends maintainability, and offers many advantages over different programming languages. Hands-On Embedded Programming with C++17 will show you how C++ can be used to build robust and concurrent systems that leverage the available hardware resources. Starting with a primer on embedded programming and the latest features of C++17, the book takes you through various facets of good programming. You'll learn how to use the concurrency, memory management, and functional programming features of C++ to build embedded systems. You will understand how to integrate your systems with external peripherals and efficient ways of working with drivers. This book will also guide you in testing and optimizing code for better performance and implementing useful design patterns. As an additional benefit, you will see how to work with Qt, the popular GUI library used for building embedded systems. By the end of the book, you will have gained the confidence to use C++ for embedded programming. What you will learn Choose the correct type of embedded platform to use for a project Develop drivers for OS-based embedded systems Use concurrency and memory management with various microcontroller units (MCUs) Debug and test cross-platform code with Linux Implement an infotainment system using a Linux-based single board computer Extend an existing embedded system with a Qt-based GUI Communicate with the FPGA side of a hybrid FPGA/SoC system Who this book is for If you want to start developing effective embedded programs in C++, then this book is for you. Good knowledge of C++ language constructs is required to understand the topics covered in the book. No knowledge of embedded systems is assumed. Downloading the example code for this book You can download the example code files for all Packt books you have purchased from your account at http://www.PacktPub.com. If you purchased this book elsewhere, you can visit http://www.PacktPub.com/support and register to have the files e-mailed directly to you.
Title from content provider.
Keywords: C++ (Computer program language); Application software -- Development.; elektronické knihy; electronic books